Analisis Humas PTPN IV PKS Tinjowan Dalam Mendukung Keberhasilan Program Corporate Social Responsibility (CSR) Terhadap Kebutuhan Masyarakat - Putri Audia Dewi; Rasyid, Abdul; Peranginangin, Indira Fatra Deni (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2025)
This study aims to analyze the role of PTPN IV PKS Tinjowan's Public Relations in supporting the implementation of the CorporateSocial Responsibility (CSR) program and its relevance to meeting the needs ofthe surrounding community. The focus of the study includes identifying the types of CSR programsimplemented, their level of suitability to the needs of residents, the sustainability oftheir implementation, as well as the obstacles and strategies for overcoming them by the Public Relations department.The research method used is qualitative with a case study approachthrough interviews, observation, and documentation. The results of the studyshow that PTPN IV PKS Tinjowan has implemented a number of CSR programsin the fields of education, health, infrastructure, and social community.However, some of the programs have not fully addressed the priority needs ofthe community due to the lack of community involvement in the planning stage. In addition, there are programs that are short-term and not yet integrated with thecompany's long-term plans. The main obstacles faced by public relations includebudget constraints, weak coordination between departments, and barriers tocommunication with the community. As a solution, public relations should increase participatory approaches with residents, strengthen internal company synergy,and propose programs based on data on community needs. This studyemphasizes the importance of the role of public relations as a communication link betweencompanies and the community in realizing beneficial and sustainable CSR programs.